EU Membership and FDI: Is There an Endogenous Credibility Effect? - Stojkov, Aleksandar; Warin, Thierry (Journal of East-West business, 2018)
The European sovereign debt crisis has increased the uncertainty regarding the benefits and costs of membership in the Economic and Monetary Union. In this article, we decided not to propose a general model but to focus on one of the important components of the European financial integration. In particular, we develop a structural gravity model, influenced by some very recent theoretical and econometric advancements. This new structural gravity approach provides needed theoretical underpinnings as well as strong support for the econometric estimation of gravity models.